Latest trends in archaeogenetic research of west Eurasians. (June 2020) - Olalde, Iñigo; Posth, Cosimo
Abstract : During the past ten years, archaeogenetic research has exponentially grown to study the genetic history of human populations, using genome-wide data from large numbers of ancient individuals. Of the entire globe, Europe and the Near East are the regions where ancient DNA data is by far most abundant with over 2500 genomes published at present. In this review, we focus on archaeological contexts that have received less attention in the literature, specifically those associated with west Eurasian hunter-gatherers as well as populations from the Iron Age and later historical periods. In addition, we emphasize a recent shift from continent-wide to regional and even site-specific studies, which is starting to provide novel insights into sociocultural aspects of past societies.